2018
DOI: 10.2478/sjph-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the DAI and ICON indices used for assessment of orthodontic treatment need in Croatian schoolchildren

Abstract: IntroductionThe aims were: evaluation of the correlation between the Dental Aesthetic Index (DAI) and Index of Complexity, Outcome and Need (ICON); the assessment of orthodontic treatment need for schoolchildren in a population with two indices, separately for schoolchildren with mixed and permanent dentition; the estimation of the population share that could not receive orthodontic treatment because of the presence of caries and/or gingivitis.MethodsA total of 2652 Zagreb school children (7 - 19 years old, 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
4
0
2
Order By: Relevance
“…In our results, we found a significant ( P < 0.001), moderate, linear correlation between the DAI score (severity of the malocclusion) and the ABO-DI score (case complexity). Similar results were found for DAI (r = 0.5523; P < 0.001) and ICON (r = 0.521; P < 0.001) scores with respect to treatment need (Onyeaso, 2007; Vidaković et al, 2018). In another study, the researchers found a moderate agreement between the ICON and dental health component of the IOTN (Borzabadi-Farahani et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…In our results, we found a significant ( P < 0.001), moderate, linear correlation between the DAI score (severity of the malocclusion) and the ABO-DI score (case complexity). Similar results were found for DAI (r = 0.5523; P < 0.001) and ICON (r = 0.521; P < 0.001) scores with respect to treatment need (Onyeaso, 2007; Vidaković et al, 2018). In another study, the researchers found a moderate agreement between the ICON and dental health component of the IOTN (Borzabadi-Farahani et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…[6][7][8][9][10][11][12][13] e previous research suggested that the ICON could replace the PAR and IOTN (15) since the ICON was developed from the PAR and IOTN and correlated highly with both of these indices. [14] Khandakji et al [15] recently concluded that the dental health component (DHC) and esthetic component (AC) of IOTN, ICON, and PAR reliably captured treatment need. e index ICON comprises five weighted measurements and owes some of its structure to IOTN and PAR.…”
Section: Introductionmentioning
confidence: 99%
“…The final ICON score was divided into malocclusion complexity grades (<29 = easy, 29–50 = mild; 51–63 = moderate, 64–77 = difficult, >77 = very difficult). A cutoff point of 43 was set to mark a definite need for orthodontic treatment [ 41 ].…”
Section: Methodsmentioning
confidence: 99%